2012
DOI: 10.1016/j.jacc.2012.02.035
|View full text |Cite
|
Sign up to set email alerts
|

2-Hour Accelerated Diagnostic Protocol to Assess Patients With Chest Pain Symptoms Using Contemporary Troponins as the Only Biomarker

Abstract: Using the ADP, a large group of patients was successfully identified as at low short-term risk of a MACE and therefore suitable for rapid discharge from the emergency department with early follow-up. This approach could decrease the observation period required for some patients with chest pain. (An observational study of the diagnostic utility of an accelerated diagnostic protocol using contemporary central laboratory cardiac troponin in the assessment of patients presenting to two Australasian hospitals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
289
0
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 368 publications
(318 citation statements)
references
References 25 publications
12
289
0
17
Order By: Relevance
“…Thereby, the high-sensitivity cardiac troponin T 1-hour algorithm was even more effective in the early triage of patients with acute chest pain than, for example, the recently developed accelerated diagnostic protocol combining the Thrombolysis in Myocardial Infarction Score with high-sensitivity cardiac troponin levels at baseline and 2 hours, or the dual-marker approach combining high-sensitivity cardiac troponin with copeptin, which assign 20%-40% of patients for rapid rule-out. [20][21][22][23][24][25][26][27] This difference is at least partly explained by the fact that the latter approaches exclusively select patients for rule-out, but do not provide guidance for rule-in.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the high-sensitivity cardiac troponin T 1-hour algorithm was even more effective in the early triage of patients with acute chest pain than, for example, the recently developed accelerated diagnostic protocol combining the Thrombolysis in Myocardial Infarction Score with high-sensitivity cardiac troponin levels at baseline and 2 hours, or the dual-marker approach combining high-sensitivity cardiac troponin with copeptin, which assign 20%-40% of patients for rapid rule-out. [20][21][22][23][24][25][26][27] This difference is at least partly explained by the fact that the latter approaches exclusively select patients for rule-out, but do not provide guidance for rule-in.…”
Section: Discussionmentioning
confidence: 99%
“…Algorytm ten umożliwiał bezpieczne wykluczenie NSTE-ACS u nawet 40% pacjentów [56][57][58]. W drugim algorytmie, opartym na strategii dwóch markerów -połączenia prawidłowego stężenia troponin sercowych z niskim stężeniem kopeptyny (< 10 pmol/l) przy przyjęciu -wykazywało bardzo dużą ujemną wartość predykcyjną dla MI.…”
Section: Dodatkowa Tabela 5 (Patrz Dodatek Internetowy) Charakterystunclassified
“…The constantly increasing sensitivity and associated higher precision of novel cTn assays allows for gradual reduction in time intervals between onset of symptoms and detection of cTn positivity [61]. Hs assays may allow reduction of the recommended 3-h intervals to 2 h [62]. However, after an attempt to further shorten the initial interval to 1½ h, investigators concluded that testing at 3 h is superior to testing at 90 min [63].…”
Section: What Constitutes the Rise And/or Fall In Ctn Concentrations?mentioning
confidence: 99%